Determination of the rate of the glutamate/glutamine cycle in the human brain by in vivo (13)C NMR - Shen, Jun (The National Academy of Sciences, 1999)
Recent (13)C NMR studies in rat models have shown that the glutamate/glutamine cycle is highly active in the cerebral cortex and is coupled to incremental glucose oxidation in an ≈1:1 stoichiometry. To determine whether a high level of glutamatergic activity is present in human cortex, the rates of the tricarboxylic acid cycle, glutamine synthesis, and the glutamate/glutamine cycle were determined in the human occipital/parietal lobe at rest. During an infusion of [1-(13)C]-glucose, in vivo (13)C NMR spectra were obtained of the time courses of label incorporation into [4-(13)C]-glutamate and [4-(13)C]-glutamine. Using a metabolic model we have validated in the rat, we calculated a total tricarboxylic acid cycle rate of 0.77 ± 0.07 μmol/min/g (mean ± SD, n = 6), a glucose oxidation rate of 0.39 ± 0.04 μmol/min/g, and a glutamate/glutamine cycle rate of 0.32 ± 0.05 μmol/min/g (mean ± SD, n = 6). In agreement with studies in rat cerebral cortex, the glutamate/glutamine cycle is a major metabolic flux in the resting human brain with a rate ≈80% of glucose oxidation.